Gaucher’s Disease – current state of knowledge and future perspectives? - Szymańska, Katarzyna; Krasnoborska, Julia; Samojedny, Sylwia; Superson, Maciej; Szmyt, Katarzyna; Walczak, Kamil; Wilk-Trytko, Klaudia; Zarębski, Łukasz (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Gaucher's Disease (GD), a rare genetic disorder, is a difficult challenge in genetic and metabolic disorders. The aim of this review is to provide an exploration of GD, spanning its pathophysiology to the latest advancements in diagnostic and therapeutic innovations. In this review we aimed to underscore the challenges it presents and the ongoing efforts to overcome them. State of knowledge: GD, characterized by the accumulation of glucocerebroside, involves molecular, cellular, and systemic dysfunctions. At the molecular level, mutations in the GBA gene give rise to diverse manifestations, influencing disease severity. Cellular disruptions lead to lysosomal dysfunction, altered calcium homeostasis, and chronic inflammation, impacting various organ systems. Diagnostic approaches involve biomarkers, genetic testing, and imaging studies, each playing a crucial role in confirming the disease type and assessing its grade. Summary: Management and treatment strategies for GD have evolved, with enzyme replacement therapy and substrate reduction therapy serving as the basics. However, challenges persist, including limited efficacy in treating neurological symptoms and the high cost of treatments. The review highlights ongoing research and future perspectives in GD therapy.